ANALISIS REVALUASI AKTIVA TETAP DAN KAITANNYA DENGAN PAJAK PENGHASILAN BADAN TERHUTANG PADA PT UNO RITEL PAPUA - Siti Roimah; Daniel Nemba Dambe (Unit Pengelola dan Pengembangan Jurnal Ilmiah dan Informasi (UPPJII) STIE Jambatan Bulan, 2019)
This study aims to determine the book value of assets after revaluation and, determine the amount of tax burden that arised after revaluation. The method used in this research is descriptive which is to examine the description of the condition of the fixed assets value of PT Uno Retail Papua. Data was collected by interview , documentation and literature review. The data analysis instruments used by calculating the difference between the fair value of fixed assets and depreciation expense after revaluation and calculate the difference between the fair value of the revaluation results as well as the book value before revaluation. For the excess of the valuation results will be subject to a Final Income Tax of 10%. The results show that the book value of fixed assets after revaluation of 3.7% compared to the book value of the previous fixed assets (ini belum final). b) The amount of income tax expense incurred when conducting a revaluation is 41.5% greater than when not conducting a revaluation.